Effects of orthodontic treatment with fixed appliances on oral health status: A comprehensive study - Kenan Cantekin; Mevlut Celikoglu; Muhammet Karadas; Hanifi Yildirim; Abdulvahit Erdem (Elsevier, 2011)
Background/purpose: The purpose of the present study was to assess changes in the oral health status in a group of young Turkish dental patients undergoing orthodontic therapy. Materials and methods: Data were obtained from clinical and radiographic examinations of 659 patients (with a mean age of 14.2 ± 1.59 years, including 39% males and 61% females), who were being treated with a fixed appliance in both arches at the Department of Orthodontics, Faculty of Dentistry, Ataturk University, Erzurum, Turkey. Changes in the decayed, missing, and filled permanent teeth (DMFT) counts and plaque index (PI) were evaluated. Statistical analysis was carried out using Wilcoxon and Mann-Whitney U tests. Results: Total DMFT counts at the time of debonding were higher than at prebonding (P < 0.05) with no gender difference. The PI showed minimum values at the beginning of orthodontic therapy and maximum values at the end of therapy. Conclusions: The results of this study showed that DMFT counts and the PI increased in a group of young dental patients undergoing orthodontic therapy, and thus patients undergoing orthodontic therapy must follow very rigid oral hygiene protocols.